Phương pháp mới tính hàm truyền rời rạc của phần liên tục trong hệ thống điều khiển số - Hy, Chu Van (Journal of Computer Science and Cybernetics, 2018)
A new method for calculating the discrete transfor function of the continuous part in digital control systems is proposed. This is very suitable for the Computer Aided Design. Several examples and applications are given.